Narrative skills in deaf children who use spoken English: Dissociations between macro and microstructural devices. (December 2016) - Jones, A.C.; Toscano, E.; Botting, N.; Marshall, C.R.; Atkinson, J.R.; Denmark, T.; Herman, R.; Morgan, G.
Highlights: Deaf children using spoken English showed equivalent performance to a hearing control group on narrative macrostructure in a task that did not depend on their receptive language skills. Deaf children's performance was poorer on narrative microstructure than the hearing group of children. Deaf children provided less complete and/or relevant answers to inference questions that assessed their understanding of the intentions and actions of the story characters. Expressive vocabulary strongly correlated with deaf children's micro-level narrative skills, but the relationship with macro-level narrative skills was weaker. Abstract: Previous research has highlighted that deaf children acquiring spoken English have difficulties in narrative development relative to their hearing peers both in terms of macro-structure and with micro-structural devices. The majority of previous research focused on narrative tasks designed for hearing children that depend on good receptive language skills. The current study compared narratives of 6 to 11-year-old deaf children who use spoken English ( N = 59) with matched for age and non-verbal intelligence hearing peers. To examine the role of general language abilities, single word vocabulary was also assessed. Narratives were elicited by the retelling of a story presented non-verbally in video format. Results showed that deaf and hearing children had equivalent macro-structure skills, but the deaf group showed poorer performance on micro-structural components. Furthermore, the deaf group gave less detailed responses to inferencing probe questions indicating poorer understanding of the story's underlying message. For deaf children, micro-level devices most strongly correlated with the vocabulary measure. These findings suggest that deaf children, despite spoken language delays, are able to convey the main elements of content and structure in narrative but have greater difficulty in using grammatical devices more dependent on finer linguistic and pragmatic skills.